Growth rings show limited evidence for ungulates' potential to suppress shrubs across the Arctic. (1st March 2022) - Vuorinen, Katariina E M; Austrheim, Gunnar; Tremblay, Jean-Pierre; Myers-Smith, Isla H; Hortman, Hans I; Frank, Peter; Barrio, Isabel C; Dalerum, Fredrik; Björkman, Mats P; Björk, Robert G; Ehrich, Dorothee; Sokolov, Aleksandr; et al.
Abstract: Global warming has pronounced effects on tundra vegetation, and rising mean temperatures increase plant growth potential across the Arctic biome. Herbivores may counteract the warming impacts by reducing plant growth, but the strength of this effect may depend on prevailing regional climatic conditions. To study how ungulates interact with temperature to influence growth of tundra shrubs across the Arctic tundra biome, we assembled dendroecological data from 20 sites, comprising 1153 individual shrubs and 223 63 annual growth rings. Evidence for ungulates suppressing shrub radial growth was only observed at intermediate summer temperatures (6.5 °C–9 °C), and even at these temperatures the effect was not strong. Multiple factors, including forage preferences and landscape use by the ungulates, and favourable climatic conditions enabling effective compensatory growth of shrubs, may weaken the effects of ungulates on shrubs, possibly explaining the weakness of observed ungulate effects. Earlier local studies have shown that ungulates may counteract the impacts of warming on tundra shrub growth, but we demonstrate that ungulates' potential to suppress shrub radial growth is not always evident, and may be limited to certain climatic conditions.